Conditions of institutional Development in Chile's Schools - María Verónica Leiva Guerrero; Diego Eduardo Astorga Fuentealba (Universidad Autónoma de Baja California, 2014)
This paper is part of a larger research study; AECID's Project A/024180/09, and pertains to an assessment of the autonomy of schools in Chile. The aim of this paper is to examine the potential for institutional development in schools in the Fifth Region of Valparaiso, Chile, by analyzing the discourses of classroom teachers and management teams from a qualitative perspective. To this end, we conducted a descriptive study with a qualitative design in five schools in the region of Valparaíso. Six focus groups were formed to collect the data, which was subsequently analyzed using discourse analysis. The results showed consensus regarding the strengths and weaknesses of the teaching-learning processes; organizational strengthening and openness toward the school's educational community. The results obtained are relevant to the national educational field and for guiding future intervention by government authorities